Pemilihan Metode Kontrasepsi Pada Ibu Pasca Bersalin Berdasarkan Media Informasi yang Digunakan Dalam Konseling - Elies Meilinawati Sri Budihartini; Etik Khusniyati; Heni Purwati; Ariu Dewi Yanti (NERSMID : Jurnal Keperawatan dan Kebidanan, 2019)
The increase in population is one of the major problems facing developing countries. One method used to reduce the rate of population growth is by implementing a family program. One of the factors that influence the choice of contraception is information. Providing information can be done with various media. The provision of information can use aids in the form of visual aids, hearing aids (audio), and hearing aids (audiovisuals). The purpose of this study was to determine the effect of information media on the selection of contraceptive methods. The design of this study is comparative analytics. The population was all postpartum mothers at BPM Hj Titik Rahmawati in Mojokerto Regency with sampling consecutive sampling technique. Data were analyzed using the chi-square test. Chi-Square statistical test results using the SPSS program obtained ρ = 0,000> α = 0.05 so that it can be concluded that there is a significant difference between the use of leaflets and video media with the selection of non-MKJP or MKJP contraceptives in postpartum mothers. Video media uses sound effects and moving images that can display directed steps, making it easier to receive the information conveyed.